Telecommunication Service Quality Assessment: A Comparative Study of Bharat Sanchar Nigam Limited and Reliance Communications Limited. (March 2013) - Jain, Pankaj
This study compared the customers' perception of quality of telecom services provided by Reliance Communications Limited (a private player) and Bharat Sanchar Nigam Limited (a public player) in western Uttar Pradesh. Using modified SERVPERF scale, thirty scale items, customers' perceptions were sought on eight aspects of service quality. In addition to standard five dimensions, three more dimensions, network quality, customer complaint and convenience, were added to the scale. Most of the research studies comparing private and public enterprises in India show that customers' level of satisfaction is comparatively more for private enterprise than that of public sector enterprise. So it was felt that Reliance Communications Limited (RCOM) would outperform Bharat Sanchar Nigam Limited (BSNL) on the measures of service quality. This contention was largely supported. The results also indicated that both groups have room for improvement.